Investigation of selected physical, biometrical and mechanical properties of Cerasus mahaleb (L.) mill in the middle Zagros forest site - Neda Sakhavati (Regional Information Center for Science and Technology (RICeST), 2012)
Cerasus mahaleb (L.) Mill is among the important broad-leaved trees in Zagros forests. Good bending property and the pleasant aroma helped the tree species to find a long history of rural and local uses. Wood consumption is closely influenced by the physical, biometric and other engineering properties. Three sound trees were harvested and tested according to ASTM-D143 standards testing procedures. Results showed that Cerasus mahaleb (L.) Mill has semi-heavy wood with high bending ability. Its compression strength parallel strain was measured as 48.45 MPa. The average fiber length and fiber diameter was 0.71 mm and 19.85 m respectively. Mean volume shrinkage and swelling was measured as 6.09% and 6.69% respectively. The radiant and tangent shrinkage and swelling after 2 and 24 hour immersion in water was 19.65%, 19.74%, 19.9%, 19.89%, 20.62% and 21.16% respectively. Mean annual diameter growth as well as mean height growth were 4.96 mm and 0.31 m respectively.